Fos expression in the brains of rats performing an attentional set-shifting task - Burnham, K.E. (Elsevier Science, 2010)
Impairments in executive function and cognitive control are a common feature of neuropsychiatric and neurodegenerative disorders. A promising behavioral paradigm for elucidating the neural mechanisms of executive function is extradimensional/intradimensional (ED/ID) shifting, which places demands on executive function by requiring the adjustment of behavioral responses based on affective or attentional information. To augment the understanding of the brain systems required for these aspects of executive function, we examined the induction of Fos protein in rats tested in the ED/ID paradigm. We found increased Fos-like immunoreactivity (Fos-LI) in several cortical areas, including medial and orbital frontal cortex (OFC), in rats performing affective or attentional shifts relative to rats performing control discriminations. However, increased Fos-LI was also present in rats that performed a yoked number of additional control discrimination trials, without affective or attentional shifting. These observations suggest that cortical networks required for affective and attentional shifting are also activated during comparable discrimination tasks that do not require shifting, consistent with a role for these networks in monitoring ongoing behavior even in situations in which adaptation to changing behavioral demands is not required.